Genetic polymorphisms in folate metabolism as risk for Down syndrome in the southern China. (18th June 2019) - Jiajin, Lin; Shuyan, Cao; Ying, Wu; Junxiao, Chen; Xiudi, Wang
Abstract: Objective: To assess the association between maternal gene polymorphisms of the enzymes involved in folate metabolism and the risk of having a Down syndrome (DS) offspring in southern China mothers. Methods: Gene polymorphisms in folate metabolizing and the levels of homocysteine (HCY) were analyzed in 84 southern China mothers with DS babies (the case group) and 120 healthy mothers (the control group). Methylenetetrahydrofolate reductase (MTHFR) C677T (rs1801133) and A1298C (rs1801131), methionine synthase (MTR) A2756G (rs1805087), and methionine synthase reductase (MTRR) A66G (rs1801394) were studied. Results: We found no significant differences ( p  > .05) in the frequencies of four genetic polymorphisms between the two groups. We found gene–gene interactions had a 1.997-fold increased risk in MTHFR 677 CT with MTR AA (OR: 1.997, 95% CI: 1.038–3.841, p  = .038) and a 2.588-fold increased risk in MTHFR 677 CT with MTRR AG (OR: 2.588, 95% CI: 1.111–6.031, p  = .028) in the case group than control. The levels of HCY were significantly higher in MTHFR 677 TT than MTHFR 677 CC in the case group (TT 17.2167±5.1051, CC 12.1969±5.0299, F  = 2.194, p  < .05), and it was significantly higher in MTHFR 677 TT in the case group than control (TT 17.2167±5.1051 in the case group, TT 10.2286±1.4373 in the control group, F  = 2.546, p  < .05). Conclusion: These results suggest that genetic polymorphisms involved in folate metabolism may have population specificity in determining the susceptibility of having DS offsprings. The gene-nutrition, gene–gene interactions and ethnicity are important variables to be considered in periconceptional nutritional supplementation and antenatal care for reducing the risk of DS babies.